Effect of Steam Delignification and Bleaching Process on Pineapple Leaf Fiber as Textile Raw Material - Warlinda Eka Triastuti; Suprapto Suprapto; Agus Surono; Mochammad Zayyan Difa Fadhillah; Regita Syahra Ramadhan; Sunia Rahma Cahyaning Tyas; Hanifah Fauziyah Zahrah (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
Pineapple is a local commodity in Indonesia that is widely cultivated. The part of the pineapple plant that is mostly used is only the fruit part, while the other plant parts are discarded and become waste. Pineapple leaves contain high fiber content of cellulose, lignin, and hemicellulose, so it is very potential if used as an alternative textile raw material. The quality of pineapple leaf fiber can be improved by going through a delignification process using an alkaline solvent with the appropriate concentration and time. This research determine the effect of delignification of pineapple leaf fiber with a solution of Sodium Hydroxide (NaOH), Hydrogen Peroxide (H2O2) and water (H2O) on tensile strength, lignin content and Scanning Electron Microscope (SEM). This research consist of six stages including delignification using 3% NaOH and 3% H2O2, washing, neutralization, preservation, and analysis of pineapple leaf fiber products. The results obtained are pineapple leaf fiber lignin test after delignification and bleaching, the best lignin results are steam delignification at 80°C with 3% NaOH solution and bleaching solution using NaOCl solution obtained 21% lignin content with a tensile strength test of 0.263 kgf/mm2. SEM analysis also showed that there was a loss of material from the fiber surface which indicated that there was degradation due to the addition of bleaching solution. This proves that alkaline treatment can also cause discoloration of natural fibers due to the removal of natural dyes in natural fibers.